Challenges for accessibility planning and research in the context of sustainable mobility - Cecília Silva; Anders Larsson (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2018)
Accessibility has become a fashionable concept both in the research and policy arena. There has been a growing interest and attention on accessibility measures and on the potential of accessibility‑based planning as means to invert the growing unsustainability of urban settlement and mobility patterns. Regardless of the potential advantages, current practice has revealed a number of challenges facing accessibility planning and research. This paper presents a reflection on two of these challenges: lack of implementation and conceptual ambiguity of accessibility measures in planning practice. After presenting the main arguments for each challenge, the paper explains how they create risks in the context of sustainable development, namely, by creating biased understandings which prevent authorities and practitioners from shifting away from the traditional "predict and provide" paradigm for transport planning. At the end of each reflection, the paper suggests a research and policy agenda to overcome the challenges supported by the institutionalisation of accessibility planning.
Keywords: 330